RISE OF THE TERRORISM AND SECESSIONISM IN SOUTH ASIA: A BAHA'I VIEWPOINT - Kidder, Rushworth M (Journal of Dharma, 2000)
Present-day humanity has reached the strange position where, although people in every country cry out for peace, it has come to think that it is impossible to achieve because selfishness and aggression will always be part of human nature. We need to move on from this kind of thinking and realize prejudice, war and unfair treatment of others have been part of humankind's growing up process. We can see that we should now progress to a period of greater maturity where we can put this childish behaviour behind us.